Effect of caffeine on foetal morphometric parameters of embryonic Wistar rat (Rattus norvegicus) - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:There is increasing body of evidence that maternal caffeine use during pregnancy predisposes the embryo and foetus to spontaneous abortion but data on its influence on foetal morphometry is scarce.Aim:This study aimed to evaluate experimentally the effects of caffeine on morphometric parameters of newborn of Wistar rats.Materials and Methods:Thirty, experimentally naive, adult female Wistar-albino rats weighing 100–150 g were mated. After confirming pregnancy by vaginal plug method, the pregnant rats were randomly assigned into four groups (Group A–D). The dams in Group A served a normal control. They had 0.2 ml/kg body weight of normal saline intraperitoneally from day 9 to 20. Experimental Group B rats had 25 mg/kg body weight of caffeine intraperitoneally. Group C had 50 mg/kg body weight of caffeine intraperitoneally and Group D dams had 100 mg/kg body weight of caffeine intraperitoneally. Dams in both experimental and control groups were sacrificed on day 20 after caffeine administration. The foetuses were weighed and their crown-rump lengths were measured. Their body mass index of the litters (foetuses) was calculated and their placentas were weighed.Results:The mean crown-rump length of the litters (Group A) was significantly more (5.61 ± 0.29) than the experimental which were 5.10 ± 0.22 cm, 4.72 ± 0.24 cm and 3.81 ± 0.16 cm for Group B, C and D litters, respectively (P< 0.0001). The mean foetal weight of Group A litters was significantly more (1.56 ± 0.38) than the experimental which were 1.25 ± 0.41 g, 1.15 ± 0.77 cm and 0.78 ± 0.34 cm for Group B, C and D litters, respectively (P< 0.0001). The mean placenta weight of the foetuses was significantly lower in the females from the experimental Group B, C and D compared to the control group (P< 0.0001).Conclusion:This study showed a significantly reduced foetal weight, crown-rump length and placenta weight in the offspring of experimental female rats treated with caffeine compared to the control.